Rooftop PV with battery storage solar smoother - Jabalameli, N.; Deilami, Sara; Masoum, M.; Abshar, M. (IEEE Computer Society, 2014)
© 2014 IEEE. Utilities are becoming concern about the increasing number of solar panels feeding unstable power into generator-based mini-grids particularly in rural locations. When the mini-grid experiences large changes in the injection of solar power, for example on cloudy days, the generators have to work hard to keep up. This paper recommends inclusion of battery storage (BS) solar smoother across terminals of existing rooftop PVs to compensate fluctuations in active output power due to environmental factors such as passing clouds and variations in solar radiation. A BS energy management strategy (BS-EMS) will be implemented to control the solar smoother and regulate the voltage at point of common coupling (PCC) while providing the grid with constant output power profile during daylight. A simple approach is also introduced and implemented to estimate battery rating based on typical measured PV characteristics.